Permanent Settlement and Outline of zamindari Life in the Hooghly region/ চিরস্থায়ী বন্দোবস্ত ও হুগলি অঞ্চলের জমিদারি জীবনযাত্রার রূপরেখা (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
After the introduction of permanent settlement, the landlords became direct owners of the land and the revenue rate was fixed permanently for them. Initially, Many zamindaris changed hands and a new class of landlords emerged on the land. Many of them living in the cities. Since the royal rate was fixed and no separate agreement was signed between the government and the farmers there was a great opportunity to collect money from the land. This abundance of the money in the life of the landlords completely changed their standard of living. Due to their good relations with the government, the landlords became a privileged classes and started living with extreme luxury and entertainment. The expression of their luxurious life started to blossom in various ways and give rise to a competition among themselves. And when the competition among the landlords increaseincreased, the expenditure on social and religious ceremonies also increase. The main burden of this increase in expenditure was borne by the common farmers, who, having no protection in the permanent settlement, were exploited by the landlords. The common poor peasants of the Hooghly District were the sole provider of all the necessity of life for the landlords. Another factor connected with the luxury of the landlords life was there since all the work was done by their subordinate, there was no shortage of time in their life. And for this reason the first steps of social reforms and nationalism emerged from among the class of landlords The earliest proponent of which was Raja Ram Mohan Roy, a resident of khanakul in Hooghly District, based on the ancient Upanishad, he declared direct war against polytheism, paganism and caste system. And based on the ancient Upanishad he declared that God is one and unique. This is a revolutionary decision of that time which was taken by him. Many superstitious Zamindar of his time not fully support Roys view, but Ram Mohan Roy proved his decision of the basic of religious documents. It was through the brahmo movement initiated by Ram Mohan Roy that the sense of patriotism and nationalism spread everywhere. This article discusses various aspects of the life and working method of the landlords in the Hooghly District region after the introduction of permanent settlement.
Keywords: Landlords; Monotheism; Renaissance; Paganism; Vaishnavism; Landowner; Baboo